Greenwashing: Strategi Bisnis yang Adaptif atau Praktik yang Merugikan Pemangku Kepentingan? - Naufal Adiwidya Ramawi; Mukhtaruddin Mukhtaruddin (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Sustainability reporting is an integral part of modern accounting practices aimed at enhancing corporate transparency and accountability regarding economic, social, and environmental impacts. In practice, greenwashing is often perceived as an adaptive business strategy in response to legitimacy pressures and stakeholder demands. This study aims to examine greenwashing practices in sustainability reporting and to assess their ethical implications from the perspective of accounting ethics. The research employs a qualitative literature review method by analyzing relevant national and international academic journal articles. The findings indicate that legitimacy pressures, agency conflicts of interest, and stakeholder demands encourage companies to engage in symbolic and selective sustainability disclosures. Although such practices may be viewed as a form of strategic adaptation, they contradict the principles of honesty, integrity, and accountability in accounting ethics and have the potential to mislead and harm stakeholders. This article emphasizes the need to strengthen accounting ethics and verification mechanisms to ensure transparent and responsible sustainability reporting.